2002
DOI: 10.1067/mva.2002.123320
|View full text |Cite
|
Sign up to set email alerts
|

Emergency surgery for thoracoabdominal aortic aneurysms with acute presentation

Abstract: Repair of thoracoabdominal aortic aneurysms with acute presentation is associated with worse outcome compared with elective cases. Nevertheless, repair may be performed with reasonable mortality and morbidity rates at specialized centers. In the acute setting, the use of surgical adjuncts is associated with improved outcome and should be used when possible. Age does not impact on survival rate in patients with acute presentation, and surgery should not be restricted to only younger patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
4

Year Published

2003
2003
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 27 publications
(42 reference statements)
0
27
0
4
Order By: Relevance
“…This experience and that reported by other investigators support use of distal aortic perfusion and spinal catheter drainage in these complex repairs. 3,4,16 The incidence of respiratory failure seems particularly high and the mortality associated with this complication was significant. Six of 11 patients having this complication eventually died.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This experience and that reported by other investigators support use of distal aortic perfusion and spinal catheter drainage in these complex repairs. 3,4,16 The incidence of respiratory failure seems particularly high and the mortality associated with this complication was significant. Six of 11 patients having this complication eventually died.…”
Section: Discussionmentioning
confidence: 99%
“…No patient is alive beyond 12 years after the procedure. Table 6 presents a comparison between results herein presented and those from Le Maire et al 16 The latter report was selected as it is one of the largest series of TAA reported, represents contemporary results, analyzes both elective and emergency cases and provides necessary details to make meaningful comparisons. The column titled 95% CI (confidence interval) compares the two reports for each element, taking the difference as the proportion in Le Maire study minus the proportion in this study using a chi square test with one degree of freedom.…”
Section: Betweenmentioning
confidence: 99%
“…Among the preoperative variables, dissections were considered acute when patients underwent surgery within 14 days of the initial event; after 14 days, dissection was considered chronic. Acute presentations were defined as patients requiring emergent or urgent operation due to acute dissection, free or contained rupture, or acute symptoms [14]. Preoperative renal insufficiency was defined as a baseline serum creatinine exceeding 3.0 mg/dl or chronic dialysis.…”
Section: Definitions Of Comparative Variablesmentioning
confidence: 99%
“…kale Kühlung bis zur Anwendung von Medikamenten.Trotz dieser sogenannten adjuvanten Maßnahmen bleibt die Mortalität und Morbidität v. a. bei Notfalloperationen hoch [15]. Eine abschließende Bewertung dieser Maßnahmen steht aus.…”
Section: Ischämie Und Reperfusion Des Intestinalen Und Hepatischen Stunclassified
“…Die vorliegende Studie hatte zum Ziel, ein Großtiermodel zu etablieren,um die Pathophysiologie des hohen Aortenclampings zu erfassen und in zukünftigen Studien adjuvante Maßnahmen objektiv überprüfen zu können. H i e r s t e h t e i n e A n z e i g e T h i s i s a n a d v e r t i s e m e n t 15 Methoden. An Schweinen wurde durch 30-minütiges Klemmen der Aorta unmittelbar distal der linken A.subclavia eine Ischämie der distalen sowie eine Hypertension der proximalen Körperpartie induziert.Metabolische und funktionelle Abstract Introduction.…”
Section: Ischämie Und Reperfusion Des Intestinalen Und Hepatischen Stunclassified